Éduquer et communiquer en matière de changements climatiques : défis et possibilités - Diane Pruneau; Mélanie Demers; Abdellatif Khattabi (VertigO)
Educating and communicating about climate change is challenging. Climate change scientific concepts are often misunderstood. People believe that climate change will have few impacts on their own life. People have difficulty to perceive gradual environmental changes. Overconsumption brings people power, pleasure and recognition. People, disconnected from nature, tend to make emotional decisions and to quickly solve environmental problems. Drawn from research, climate change communication and education strategies are presented for helping learners to better understand climate change, communicating the urgency to act, motivating the adoption of mitigation behaviours and reinforcing people’s skills for implementing adaptations.